Internet Of Things (Iot) Light Control System Using a Mobile-Based Raspberry Pi - Ben, Azim; Adly, Embara; Hasannah, Devia (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2020)
Internet of thing (IoT) is a concept that aims to expand the benefits of internet connectivity that is connected continuously. Internet of things (IoT) can be used in buildings to control electronic equipment such as room lights that can be operated remotely via a computer network. This study aims to build a remote control device by utilizing internet technology to carry out the mobile-based light control process. The research was conducted by building a prototype and mobile-based application using the python programming language. In this study, there is a control feature, namely one light control which is used to turn on one lamp and two controls used to turn on the lamp simultaneously.